The earliest parietal representations in the cantabrian region from a cognitive perspective: a theoretical approach to the symbolism (Salduie, 2024)
Cognitive Archaeology tends to use borrowed constructs from Psychology in order to analyze the kind of mind which underlies the archaeological record evidence. In this case, a brief approach to the earliest palaeolithic graphic cave representations, characterized by red color and figurativeness absence, will be carried out under the main cognitive capacities’ perspective in the modern human mind. To this purpose it will be analyzed the nature of the primary capacities and their combination into the emergent ones, to apply them to the cave art representations. As a conclusión it is possible to support that the style of many representations is influenced by our neurobiological characteristics, and that cognitive capacities neccesary to carry out the earliest non-figurative representations were already present in Homo neanderthalensis.
Keywords: Cognitive Archaeology; Cave art; Symbolism; Behavioural modernity